The assessment of the basic competences - Polo Martínez, Ignacio (Avances en Supervisión Educativa, 2010)
Though there is a provision for the assessment of the basic competences in the Education Law in force at present, the Organic Act 2/2006, as well as in every one of the regulations that settle an specific curriculum for each one of the autonomous regions in Spain, there are still some lacks which the present article intends to point out and, consequently, offer a well-intended proposal to help find a possible solution to the deficiencies revealed.